Challenging Ableist Norms: Old Age, Disability, and its Impact on Family Dynamics in Rohinton Mistry's Family Matters - T, Mary Job; Thomas, Dr. Christine Ann (South Eastern European Journal of Public Health, 2025)
This paper explores the intersection of old age, disability, and family dynamics in Rohinton Mistry's Family Matters through the lens of social constructionism. It subverts existing ableist norms that are nurtured through a conventional social lens. This study examines the effects of societal perceptions on disability and aging. These, in turn, affect familial relationships and individual identities. The analysis is fortified through the social constructionism theory of Peter Berger and Thomas Luckmann. This article delves into textual analysis and discusses subjectivity and objectivity with reference to the agonizing experiences of elderly people with disabilities within their families, the detrimental effects of ableism on mental and physical well-being, issues with family identity, and the complex and wide-ranging effects of discrimination against families with members who have disabilities. It affords a space to deliberate on existing societal perceptions of normalcy and functionality in contrast to the perspective posited by Berger and Luckman. The paper posits how 'social stock of knowledge' and 'zones of familiarity’ influence the experiences of Nariman Vakeel, an elderly patriarch suffering from Parkinson's disease, whose physical decline forces his family to confront deep-rooted prejudices and expectations surrounding care, dependency, and the value of life in old age. By applying social constructionism, the analysis delves into how disability is not merely a biological condition but is shaped by cultural, social, and familial responses. The novel exposes the tension between the societal expectation of independence and the reality of vulnerability and how these constructs influence the treatment of the elderly and disabled.